Topographical distribution and morphology of NADPH-diaphorase-stained neurons in the human claustrum - Hinova-Palova, Dimka V.; Edelstein, Lawrence; Landzhov, Boycho; Minkov, Minko; Malinova, Lina; Hristov, Stanislav; Denaro, Frank J.; Alexandrov, Alexandar; Kiriakova, Teodora; Brainova, Ilina; Paloff, Adrian; Ovtscharoff, Wladimir (Frontiers in Systems Neuroscience, 2014)
We studied the topographical distribution and morphological characteristics of NADPH-diaphorase-positive neurons and fibers in the human claustrum. These neurons were seen to be heterogeneously distributed throughout the claustrum. Taking into account the size and shape of stained perikarya as well as dendritic and axonal characteristics, Nicotinamide adenine dinucleotide phosphate-diaphorase (NADPHd)-positive neurons were categorized by diameter into three types: large, medium and small. Large neurons ranged from 25 to 35 μm in diameter and typically displayed elliptical or multipolar cell bodies. Medium neurons ranged from 20 to 25 μm in diameter and displayed multipolar, bipolar and irregular cell bodies. Small neurons ranged from 14 to 20 μm in diameter and most often displayed oval or elliptical cell bodies. Based on dendritic characteristics, these neurons were divided into spiny and aspiny subtypes. Our findings reveal two populations of NADPHd-positive neurons in the human claustrum—one comprised of large and medium cells consistent with a projection neuron phenotype, the other represented by small cells resembling the interneuron phenotype as defined by previous Golgi impregnation studies.